DIGITAL INTEGRATED CIRCUITS A DESIGN PERSPECTIVE - Rabaey, Jan M.; Chandrakasan, Anantha P.; Nikolic, Borivoje (Pearson India Education Services Pvt. Ltd, 2016)
Progressive in content and form, this text successfully bridges the gap between the circuit perspective and system perspective of digital integrated circuit design. Beginning with solid discussions on the operation of electronic devices and in-depth analysis of the nucleus of digital design, the text maintains a consistent, logical flow of subject matter throughout. The revision addresses today's most significant and compelling industry topics, including: the impact of interconnect, design for low power, issues in timing and clocking, design methodologies, and the tremendous effect of design automation on the digital design perspective. The revision reflects the ongoing evolution in digital integrated circuit design, especially with respect to the impact of moving into the deep-submicron realm.